1989
DOI: 10.1016/0091-3057(89)90353-5
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to and conditioning with apomorphine in pigeons

Abstract: Pigeons that repeatedly experienced the effect of apomorphine in the same environment showed an augmented behavioural response to the same drug dose as compared with controls that experienced the effect of the drug dose in differing environments. Sensitization, an increase in the behavioural response that is observed in pigeons when the same dose of apomorphine is repeatedly administered, may thus be mainly due to a conditioning of the drug response to incidental environmental cues. Apomorphine injections also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The present experiment was simply not designed to assess a mere conditioned response enhancement but was instead aimed at measuring a conditioned discriminative responding. It is pertinent here that pigeons, like rodents, have also been shown to prefer to revisit a cage in which they were previously treated with apomorphine than to revisit one in which they were previously treated with saline (place conditioning; Burg et al 1989). This indicates that apomorphine administration, besides eliciting a pecking response has a rewarding effect, a circumstance that is in line with much evidence that dopaminergic transmission is heavily implicated in the neural signalling of reward (Wise and Rompre 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The present experiment was simply not designed to assess a mere conditioned response enhancement but was instead aimed at measuring a conditioned discriminative responding. It is pertinent here that pigeons, like rodents, have also been shown to prefer to revisit a cage in which they were previously treated with apomorphine than to revisit one in which they were previously treated with saline (place conditioning; Burg et al 1989). This indicates that apomorphine administration, besides eliciting a pecking response has a rewarding effect, a circumstance that is in line with much evidence that dopaminergic transmission is heavily implicated in the neural signalling of reward (Wise and Rompre 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments carried out in our laboratory have consistently shown that in pigeons the sensitization, or more precisely the IR, that develops upon repeated administration of apo is strongly cage-environment specific (Experiment 4; Burg et al, 1989;Godoy and Delius, 1999;Keller and Delius, 2001;Acerbo et al, 2003a; cf. also Akins and Geary, 2008, cocaine in quail).…”
Section: Conditioned Sensitizationmentioning
confidence: 94%
“…The overall results support the view that differences in apo responsiveness of pigeons have a genetic background. Experiment 4: sensitization context specificity Burg et al (1989) suggested that the sensitization to apo was context dependent, in the sense that the IR that had been induced in one kind of distinctive experimental cage did not transfer to a markedly different kind of experimental cage. This is in agreement with the results of experiments in which a reduction of the day 1 response to apo brought about by coadministration of dopamine antagonists was correlated with a lesser response increment until day 6 and a smaller response after saline-only treatment on day 7 (Acerbo et al, 2003a;Acerbo and Delius, 2004; see also Discussion of Experiment 8).…”
Section: Experiments 3: Selected Parentagementioning
confidence: 99%
See 2 more Smart Citations